Shared and distinct biological circuits in effector, memory and exhausted CD8 + T cells revealed by temporal single-cell transcriptomics and epigenetics - Giles, Josephine R; Ngiow, Shin Foong; Manne, Sasikanth; Baxter, Amy E; Khan, Omar; Wang, Ping; Staupe, Ryan; Abdel-Hakeem, Mohamed S; Huang, Hua; Mathew, Divij; Painter, Mark M; Wu, Jennifer E; et al. (Nature immunology, 2022)
Naïve CD8 T cells can differentiate into effector (T ), memory (T ) or exhausted (T ) T cells. These developmental pathways are associated with distinct transcriptional and epigenetic changes that endow cells with different functional capacities and therefore therapeutic potential. The molecular circuitry underlying these developmental trajectories and the extent of heterogeneity within T , T and T populations remain poorly understood. Here, we used the lymphocytic choriomeningitis virus model of acute-resolving and chronic infection to address these gaps by applying longitudinal single-cell RNA-sequencing (scRNA-seq) and single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) analyses. These analyses uncovered new subsets, including a subpopulation of T cells expressing natural killer cell-associated genes that is dependent on the transcription factor Zeb2, as well as multiple distinct TCF-1 stem/progenitor-like subsets in acute and chronic infection. These data also revealed insights into the reshaping of T subsets following programmed death 1 (PD-1) pathway blockade and identified a key role for the cell stress regulator, Btg1, in establishing the T population. Finally, these results highlighted how the same biological circuits such as cytotoxicity or stem/progenitor pathways can be used by CD8 T cell subsets with highly divergent underlying chromatin landscapes generated during different infections.